2010
DOI: 10.1210/jc.2009-0570
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Insulin-Like Growth Factor (IGF)-I Treatment in Short Children with Low IGF-I Levels: First-Year Results from a Randomized Clinical Trial

Abstract: rhIGF-I treatment was associated with age- and dose-dependent increases in first-year height velocity. Adverse events during treatment were less common than in previous studies and were generally transient, easily managed, and without known sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 28 publications
8
53
3
Order By: Relevance
“…at the upper limit of international recommendations (39); accelerated bone maturation compared with the control group (1.1 and 1.2 vs 0.8 years), and a significantly greater number of children entering puberty (12 vs 1). However, this study (8) demonstrates the efficacy of rhIGF1, with a growth rate increase in both dosage groups (7 and 7.9 vs 5.2 cm/year in controls) and increased height (C0. 4 The prevalence of severe primary IGFD defined using criteria for rhIGF1 treatment was only 1.2% in a vast cohort of children with short stature.…”
Section: European Journal Of Endocrinologymentioning
confidence: 52%
See 2 more Smart Citations
“…at the upper limit of international recommendations (39); accelerated bone maturation compared with the control group (1.1 and 1.2 vs 0.8 years), and a significantly greater number of children entering puberty (12 vs 1). However, this study (8) demonstrates the efficacy of rhIGF1, with a growth rate increase in both dosage groups (7 and 7.9 vs 5.2 cm/year in controls) and increased height (C0. 4 The prevalence of severe primary IGFD defined using criteria for rhIGF1 treatment was only 1.2% in a vast cohort of children with short stature.…”
Section: European Journal Of Endocrinologymentioning
confidence: 52%
“…Growth rates increased by 5.4-6.1 cm/year according to the dosage (80 mg/kg-120 mg/kg per 12 h) (38). A single study evaluated the efficacy of rhIGF1 given for 1 year to children with ISS (8). These results indicate a need for caution regarding several points such as the mean IGF1 SDS increases of C2 (80 mg/kg) or C2.2 (120 mg/kg), i.e.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…73 There was no rhGH-treatment comparison group in that study, although it has been suggested that rhGH treatment of children with ISS may be expected to produce a more positive effect on adult height as it does not lead to advancement of osseous maturation compared with controls. The mean increments in growth velocities attained in this study (1.8cm/year and 2.7cm/year for the two treatment groups) have also been noted to be lower than the growth velocities achieved in patients with severe IGF-1 deficiency due to GH insensitivity treated with rhIGF-1 at the same doses (5.4 and 6.1cm/year, respectively).…”
Section: Recombinant Human Insulin-like Growth Factor-i Height Attainmentioning
confidence: 90%
“…The reports of IH in children with severe GH insensitivity (Laron syndrome) and children with low insulin-like growth factor 1 (IGF-1) treated with recombinant IGF-1 (19,20) suggest that exposure to IGF-1 may be the pathophysiologic mediator of the rhGH effect. Increased cerebrospinal fl uid (CSF) production, decreased CSF absorption, changes in CSF fl ow, or a combination of these factors have been postulated (21,22) .…”
Section: Discussionmentioning
confidence: 99%